2015
DOI: 10.1007/s00167-015-3888-x
|View full text |Cite
|
Sign up to set email alerts
|

Femoral tunnel enlargement after anterior cruciate ligament reconstruction using RigidFix compared with extracortical fixation

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…They showed that biomechanical properties were superior to other femoral fixation devices in hamstring ACL surgery, although Rose,et al [36] confute their hypothesis that the trasfixation technique leads to less laxity and therefore to a better clinical outcome when compared with the use of bioabsorbable screws. According to a recent study by Lopes et al, greater enlargment of the femoral bone tunnel was observed when a bioabsorbable trans-tunnel pin system was used with medial portal technique, compared to extracortical fixation [37]. Will a shorter graft and more rigid graft complex fixation produce less tunnel enlargement?…”
Section: Discussionmentioning
confidence: 99%
“…They showed that biomechanical properties were superior to other femoral fixation devices in hamstring ACL surgery, although Rose,et al [36] confute their hypothesis that the trasfixation technique leads to less laxity and therefore to a better clinical outcome when compared with the use of bioabsorbable screws. According to a recent study by Lopes et al, greater enlargment of the femoral bone tunnel was observed when a bioabsorbable trans-tunnel pin system was used with medial portal technique, compared to extracortical fixation [37]. Will a shorter graft and more rigid graft complex fixation produce less tunnel enlargement?…”
Section: Discussionmentioning
confidence: 99%
“…Another observation in our study was tunnel widening increased from 3 months to six months and then either remained constant or reduced in size. Other devices like rigid fix have been found to have greater degree of tunnel enlargement than endobutton as observed by Lopes et al & hence they were not considered [14] . Compression system also can have the tunnel widening if the graft is not fixed near the joint line leading to stress shielding of the unloaded proximal bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, in all types of interference screws, the postoperative tunnel enlargement problem exists [4]. Depends on the level of local enlargement, it has been shown that the tunnel enlargement can affect the outcome of ACL reconstruction and complicate its revision surgery [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well-known that the tunnel local or cross-sectional region could widen in the first 12 weeks post-operation [4]. Furthermore, the researches on both tibial and femoral tunnel growth shown that after auto-graft ACL reconstruction the mechanical instabilities are the main contributed factor [5,8].…”
Section: Introductionmentioning
confidence: 99%